Sectoral Energy- and Labour-Productivity Convergence - Peter Mulder; Henri L.F. de Groot (Tinbergen Institute, 2004)
This paper provides an empirical analysis of energy- and labour-productivity convergence at a detailed sectoral level for 14 OECD countries, covering the period 1970-1997. A f\~a-convergence analysis shows that the development of cross-country variation in productivity performance depends on the level of aggregation. Both patterns of convergence as well as divergence are found. A fÒ-convergence analysis provides support for the hypothesis that in most sectors lagging countries tend to catch up with technological leaders, in particular in terms of energy productivity. Moreover, the results show that convergence is conditional rather than unconditional, meaning that productivity levels converge to country-specific steady states, and that cross-country differences of energy-productivity levels are substantially larger than of labour-productivity levels at all levels of sectoral aggregation. Finally, searching for the fundamentals determining cross-country productivity differentials reveals a positive productivity effect of energy prices and economies of scale in several sectors, while wages, investment share, openness and specialization play only a very limited role in explaining (cross-country differences in) energy- and labour-productivity growth.
Keywords: O13; O47; O5; Q43; 330; energy productivity; labour productivity; convergence; sectoral analysis; Energiekonsum; Produktivität; Arbeitsproduktivität; Branche; OECD-Staaten